IMPROVING SECURITY OF IOT DEVICE COMMUNICATION USING MODIFIED HASHING SOLUTION - Rao, B Bamleshwar; Waoo, Akhilesh A (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Advancements in technology have led to the invention of outfits, and the number of devices is increasing every day. Diligence is introducing new devices day by day and prognosticating that 50 billion devices will be connected by 2022. These devices are stationed through the Internet, called the Internet of Things (IoT). The operation of IoT devices is weather prediction, covering surgery in hospitals, identification of creatures using biochips, furnishing shadowing connectivity in motorcars, smart home appliances, etc. IoT devices have limitations related to security at both the software and hardware ends. In the IoT paradigm, Internet-connected embedded devices manipulate sensitive user-related data and require acceptable security results. The security results designed for network-enabled embedded devices must address issues like vacuity and usability, taking into consideration the low computational capabilities and low consumption conditions of IoT appliances. Authentication is the process of vindicating a reality’s identity. Best security practices state that authentication protocol should involve at least two different types of credentials. Authentication in IoT is a bit challenging because the realities involved in the IoT terrain cannot afford to include cryptographic savages which have high computational complexity as in the traditional internet. The most recent secure hash algorithm fashion formalized by the NIST is SHA-3. SHA-3 is fully appropriate to ensure authentication for a sender and receiver transaction. The presented paper includes a deep literature review on IoT security issues and proposes a new modified hash algorithm, which is more efficient in device communication security.